Calculation of Sediment Accumulation Volume in Aparan Reservoir (London Journal of Research In Science: Natural and Formal, 2023)
Long-term and efficient operation of a reservoir largely depends on the correct solution of problems considering such principal aspects as the forecast of fluid and solid river flows, taking into account climatic and anthropogenic factors; the evaluation of the amount of sediment deposited in the reservoir; the prediction of the possible accidents scenario and assessment of their consequences. The purpose of this paper is to determine the volume of eventually accumulated soil mass in a reservoir. As an example, the calculations are given for the Aaparan Reservoir located in the Republic of Armenia. The study has been based on the initial hydrometric data on the flow rate and sediment load, the design characteristics of the reservoir. Three principal methods have been chosen for the calculated estimation of the deposited sediment volume. Field measurements in the Aparan reservoir were carried out using precise geodetic means. Comparison of the obtained calculation results and field measurements enables to assess the reliability of the calculation methods, and to reveal the inaccuracies of a number of initial data. Despite the significant discrepancy between the obtained values of the deposited silt volume, the recorded maximum value does not exceed 1.5% of the reservoir useful volume. The calculation results make it possible to arrive at a conclusion that over half a century of operation, the design parameters of the Aparan reservoir remain practically unchanged. This proves that the Kasakh River, which flows into the reservoir, has a very weakly expressed alluvial regime.
Keywords: flow; reservoir; stream; hydrometric data; silt; sediment; useful volume; dead volume.